World cheese book - Aspinwall, Martin (DK, 2015)
"World Cheese Book shows you how to enjoy more than 750 of the world's finest cheeses and includes tasting notes and serving tips. World Cheese Book is the comprehensive guide to cheese and covers more world cheeses, with more photography, than any other book on the subject. Discover the flavor profile, shape, and texture of just about every imaginable cheese in this exhaustive, at-a-glance reference. Written by a team of experts, each writing about their own region, World Cheese Book is a treasure trove of information for the truly adventurous cheese lover and a complete guide to the world of cheese. A tour of the finest cheese-producing countries reveals local traditions and artisanal processes -- from Europe, the United Kingdom, and Scandinavia to the Americas to Asia, Australia, and New Zealand. Images of each cheese (inside and out) give an up-close view of each variety. Step-by-step techniques show how to make cheese in your own kitchen. Complementary food and wine pairings round out the offerings in World Cheese Book with the best part of all: Learning how best to enjoy eating these uniquely wonderful cheeses."--